Sugarcane Root Distribution in the Soil Profile at the White Nile Sugar Estate Plantation - Muataz Shareif Mohammed Ali; Mukhtar Ahmed Mustafa; Amir Bakheit Saeed (Agricultural Sciences: Techniques and Innovations Vol. 1, 2025)
The plant root system depth is crucial as it determines the potential depth of soil available for water and nutrient uptake by the crop. When roots are shallow, the plants can only take water from a small depth of soil; later, as the roots grow, roots can take water from an increasing depth of soil. Consequently, the interval of irrigation water should be applied frequently at the young stage and in long intervals at the end of the season. Accordingly, the root system distribution of the sugarcane crop was studied for the plant cane and ratoon crop at the three developmental stages at the White Nile Sugar Company fields. The study revealed that, the rooting depths of plant cane in the first season (2011/2012) for the development (DEV), middle (MID) and maturity (MAT) stages were 40, 50 and 50 cm, respectively, and in the ratoon crop in the second season (2012/2013) the rooting depths for the consecutive stages were 40, 40 and 50 cm.